Demonstration of Epstein-Barr Virus by In Situ Hybridization in Papillary Thyroid Carcinomas Developing on Background of Hashimoto’s Thyroiditis - Karaarslan, Serap; Kasap, Esin; İpek, Fatma Nur; Akyıldız, Mahir (Experimental and Clinical Endocrinology & Diabetes, 2024)
Aim This study aimed to demonstrate the role of Epstein-Barr Virus (EBV) in papillary thyroid carcinomas (PTC) developing on the background of Hashimotoʼs thyroiditis (HT).Methods The presence of EBV in tumoral tissue, lymphocytes, and peritumoral normal thyroid tissue was investigated using the in situ hybridization method in paraffin blocks. The subtypes of PTC, tumor diameter, TNM stage, multifocality, invasion of thyroid capsule, perineural invasion, and muscular tissue invasion were identified and compared according to EBV involvement.Results Eighty-one patients with HT diagnosis, with 93.8% (n=76) female and 6.2% (n=5) male, were included in the study. Papillary microcarcinoma was the pathological diagnosis in 24.2% (n=15) of the cases. EBV was identified in 58.06% (n=36) of the tumor cells nuclei, 58.06% (n=36) in the tumor cell cytoplasm, 16.12% (n=10) in tumor infiltrative lymphocytes, and 53.2% (n=33) in normal parenchymal follicle epithelial cells (NPFEC). In the T2 stage, the rate of EBV nuclear positivity in patients was significantly higher (p=0.034). The classic variant of papillary carcinoma was accompanied by a significantly higher rate of EBV-negative NPFEC (67.6%, p=0.049). In multifocal tumors, EBV positivity was found to be significantly higher in lymphocytes in the surrounding tissues (58.3%, p=0.034).Conclusion A significant increase in EBV positivity in the surrounding tissue lymphocytes was observed in multifocal PTC developing on a background of HT. This suggests a possible association between HT and EBV.
Keywords: Epstein-Barr virus; thyroid papillary carcinoma; Hashimoto thyroiditis; microcarcinoma; multifocality